Antitumor, antioxidant and antibacterial evaluation of new ligand of cinnemaldehyde and its Fe (III) and Mn (II) complexes - Taravat Talebi; Pegah Namian; Karimollah Ghasemi Germi; Fahmideh shabani; Armin Talebi; Seyed Reza Mirhafez (International Journal of Phytomedicine, 2012)
Cinnamomum zeylanicum is medicinal plant posse’s significant biological activities. In this study, we investigated biological properties of the ligand and metal complexes synthesized from herb of C.zeylanicum (cinnemaldehyde) by chemical reactions. N4 [(E, 2E)-3-Phenyl-2-propenylidene] isonicotinohydrazide abbreviated as NI were synthesized as ligand. Fe (III) and Mn (II) metal complexes of this ligand prepared. Characterization of the ligand and its complexes were made by microanalyses, 1H NMR, 13C NMR, FT-IR and UV–Visible spectroscopy. Cytotoxic, antioxidant and antibacterial activities of these compounds have been evaluated by MTT, DPPH, agar disc diffusion and agar dilution assays, respectively. These new compounds showed high Cytotoxic effect against K562, Jurkat and T47D cell lines. Our results showed that the metal complexes and their ligand, had weak antioxidant potential with RC50 value of 0.394, 0.724 and 1.429 mg/mL, respectively. The Fe (III) complex had the highest cytotoxic effects on K562, Jurkat and T47D with IC50 value of 86.12, 77.86, 118.52, respectively. The Fe (III) complex had the highest antibacterial activity and ligand and Mn (II) complex were in next levels.